KISI-KISI SOAL DAN ANALISIS DALAM EVALUASI PENDIDIKAN - Achmad Rasyid Ridha; Miftahurohman; Lalu Firman Hadiwijaya (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Educational evaluation plays a strategic role in measuring the achievement of learning objectives and serves as a basis for decision-making to improve the learning process. The quality of evaluation is strongly influenced by the assessment instruments used, particularly through the development of test blueprints and the implementation of item analysis. This article aims to examine the role of test blueprints and item analysis in improving the quality of educational evaluation. The method employed is a literature review of relevant theoretical frameworks and recent national and international research findings. The discussion reveals that test blueprints function as systematic guidelines in planning assessment instruments to ensure alignment with competencies, content, and cognitive levels, thereby supporting content validity. Meanwhile, item analysis—both qualitative and quantitative—plays a crucial role in empirically evaluating item quality through indicators such as difficulty index, discrimination power, distractor effectiveness, and test reliability. The integration of well-designed test blueprints and systematic item analysis has been shown to enhance assessment objectivity, reduce teacher subjectivity, and provide a more accurate representation of students’ abilities. Therefore, the consistent application of these two components is a fundamental requirement for conducting valid, reliable, and quality-oriented educational evaluations.